2012
DOI: 10.1177/1359105312454909
|View full text |Cite
|
Sign up to set email alerts
|

Symptom experiences in patients after heart transplantation

Abstract: Patients' perceptions of immunosuppression-related symptom experience impact on quality of life and medication adherence. Using The Modified Transplant Symptom Occurrence and Symptom Distress Scale capturing items on symptom occurrence and symptom distress, 261 heart transplant recipients reported on their symptom experiences. Symptoms occurring with the highest prevalence were tiredness, lack of energy, and nervousness. Men showed erectile dysfunction causing the most distress. Women and younger patients repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 38 publications
(63 reference statements)
1
25
2
7
Order By: Relevance
“…A subsequent study undertaken with 216 heart transplant recipients demonstrated the internal consistency of this scale. Internal consistency was high for the symptom occurrence (.947) and symptom distress (.984) subscales [19]. …”
Section: Methodsmentioning
confidence: 99%
“…A subsequent study undertaken with 216 heart transplant recipients demonstrated the internal consistency of this scale. Internal consistency was high for the symptom occurrence (.947) and symptom distress (.984) subscales [19]. …”
Section: Methodsmentioning
confidence: 99%
“…In a Canadian study published in 2010 using the SF-36 to assess pain in 92 heart transplant recipients, the results showed that 46% of patients reported at least mild pain and 21% reported moderate to severe pain (14) . Moreover, physical symptoms, such as fatigue, lack of energy, and nervousness, are associated with patients' perceptions after heart transplant and may last more than one year after surgery, which can be a barrier to patients achieving better QOL by affecting their mental, social, and physical well-being (15) . These data are in agreement with the present results, which showed no statistically significant difference in bodily pain or role-physical dimensions between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Las complicaciones psicológicas más comunes son los trastornos del estado de ánimo y dentro de éstos, los trastornos depresivos, con una prevalencia que oscila entre el 10 y el 58% 22,24 . La depresión es un problema clínico de gran importancia, ya que puede ser un factor de riesgo para las conductas de no adherencia al tratamiento, lo que provoca a su vez el rechazo del órgano, una disminución de la calidad de vida y un aumento de su morbi-mortalidad en un alto porcentaje de pacientes 21,22,[24][25][26][27][28][29][30] .…”
Section: Las Repercusiones Psicológicasunclassified
“…Por un lado, pierden la seguridad que les proporciona la atención hospitalaria, lo que los lleva a pensar en el riesgo de infección, rechazo y muerte. Y, por otro lado, tras el alta, los familiares suelen distanciarse de ellos debido a que consideran que los pacientes han regresado a una vida normal 21,22,[24][25][26][27][28][29][30] . Así, en un estudio que realizaron Kugler y col 26 observaron que, a los tres años postrasplante, el 9% de los pacientes tenía un nivel de ansiedad grave.…”
Section: Las Repercusiones Psicológicasunclassified
See 1 more Smart Citation